Historiography of the major English-language studies of death, afterlife, and memorial rites in Buddhism - Gunskii Aleksey (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article reviews the main English-language works devoted to the study of "Buddhist death": ideas about death, the afterlife, funeral and memorial rites in the countries where Buddhism is widespread. Considerable attention is paid to the description of the methodological approaches developed in these works. The studies are classified into three groups according to the regional principle: Japanese Buddhism, Tibetan Buddhism, Buddhism in other Asian countries. Publications on Japanese Buddhism are reviewed in chronological order in accordance with the main stages of Japanese history. For the period of the early Japanese Middle Ages, rituals aimed at achieving birth in the Pure Land of Buddha Amida are described. In the period of the mature and late Middle Ages, the classical Japanese funeral rite was formed, the central part of which is the posthumous tonsure of the deceased as a monk and ritual posthumous enlightenment. At the same time, a developed system of long-term memorial rites is formed. For modern Japan, the problem of "funeral Buddhism" is described, related to the fact that the main activity of Japanese institutional Buddhism is reduced to conducting funeral rites, and it also brings the temples the main income. The sections devoted to Tibet and other Asian countries briefly describe studies examining ideas about death and funeral rites in these regions. Among the methodological approaches, the main attention is paid to the ideas of J. Stone. She suggests considering Buddhism not as a single unified system, but as a reservoir of symbolic resources to which people resort in their specific life circumstances to understand the problems of life, death and other existential issues. The presented review can be considered as a brief introduction to the field of "death studies" in relation to the Buddhist regions of Asia.